Conflict in resource management for ecosystem services: water in Lashi Watershed, Lijiang - Yu Xiaogang (2001)
Water supplied free to urban centres imposes costs on the upland watershed. The paper analyses the conflicts and costs of such provision of external ecosystem services in a case in Yunnan, China. It argues that in order to internalise the external costs of such water supply, there should be a locally embedded system of forest management. It further argues that pricing of these external ecosystem products, like water, is needed to enable local communities to balance the benefits from their sale against costs and other benefits. - Reproduced
Keywords: Watersheds - China; Water supply - China; Water supply